Yo soy de p fkn r - Derrek Powell (Borealis: An International Journal of Hispanic Linguistics, 2022)
Based in a sociophonetic analysis of lyrics performed by eight male Reggaeton artists of Puerto Rican origin, this study combines raciolinguistic and variationist frameworks to examine the frequency of occurrence and underlying linguistic, musicological, and poetic factors conditioning the distribution of the lateral variant of syllable- and word-final alveolar tap /ɾ/. Given that this trait is regarded as a distinctive characteristic of Puerto Rican Spanish capable of indexing in-group membership alongside positive assessments of Puerto Rican national identity, the study explores the implementation of this feature in popular performances of Puerto Ricanness in the context of global Latin Urban Music (Delgado Díaz et al. 2021, Medina Rivera 1997, Valentín Márquez 2015).The results show that lateralization is more frequently used by contemporary reggaetoneros like Bad Bunny and Ozuna, whose professional careers began in an era in which Reggaeton enjoyed global accessibility, contrasted to the pioneering artists of the genre such as Daddy Yankee and Nicky Jam, who use the variant significantly less frequently. Additionally, the results suggest that, while the most recent tracks performed by newer artists exhibit the highest rates of occurrence, the inverse is true for artists whose careers began in the early 2000s before the global consumption of Reggaeton, who are documented as decreasing use of [l] in what is interpreted as an attempt to distinguish their works from younger performers. This work contributes to the growing literature regarding the linguistic construction of performative identities permeating the popular music industry, offering insight into the racialization of [l] as a distinct Puerto Rican feature relative to expressions of ethnonational pride